The power of your subconscious mind - Murphy, Joseph , 1898-1981; Pell, Arthur R. (Prentice Hall Press, 2011)
Examines the connection between the mental dynamics of thinking in relation to one's quality of life while offering simple techniques designed to create new, more innovative thought processes and stimulate creativity, in a revised and expanded edition of the best-selling work